Comparison of accuracy of maxillary dentition defect models acquired through digital impression and traditional pressure impression - HU Shuai, FANG Qing, LU Qiyuan, TAO Jianxiang (Editorial Office of Stomatology, 2024)
Objective To compare the accuracy of maxillary dentition defect models obtained by digital impression and traditional pressure impression, analyzing the influencing factors. Methods Twenty patients with maxillary dentition defects(25 free ends and 18 non-free ends)were selected. Digital impression and traditional pressure impression were utilized to fabricate models of maxillary dentition defects. Digital impressions were obtained through intraoral scanning(TRIOS2, 3Shape). For the same patient, traditional pressure impression and perfusion plaster model were used for window scanning(SHINING 3D), and the resulting STL format digital model was exported. In Geomagic Control X software, conversion fit and best fit analyses were conducted on the two digital models using the remaining abutment as reference landmarks. The total deviation(T) between the two digital models was measured, and positional deviations of the alveolar crest in mesial(M), central(C), distal(D), and maxillary palate(P)regions of the defect area were calculated. A comparison was made between free end defect area and non-free end defect area, followed by statistical analysis using t-test. Results When the remaining abutments were utilized as reference points for conversion fitting, the total deviation between the two digital models was measured at 0.03 mm, while the positional deviations of M, C, D, P positions amounted to 0.47 mm, 0.65 mm, 1.48 mm and 0.07 mm respectively. In the best fitting, the total deviation between the two digital models was 0.03 mm, while the positional deviations of M, C, D, P, were measured to be 0.50 mm, 0.66 mm, 1.43 mm and 0.08 mm respectively. The two fitting methods exhibited no statistically significant distinction(P>0.05). The comparison results between the free end defect area and the non-free end defect area revealed that the mean deviations of C and D sites in the free end defect area were 1.07 mm and 2.38 mm, respectively, which exceeded those observed in the non-free end defect area(0.08 mm and 0.11 mm, P<0.05) with statistically significant difference. Conclusion The digital impression for maxillary dentition defect model exhibits a greater deviation compared to the traditional pressure impression model, particularly in the central and distal regions of the free end defect area.